Wedding Songs of the Novgorod Region: To the Issue of the Tunes Territorial Distribution - Inga V. Korolkova (Современные проблемы музыкознания, 2025)
The musical features of wedding rituals of the Novgorod region have only been fragmentarily studied to date in terms of the territorial distribution of melodies. This article aims to fill this gap. The article is based on materials obtained from folklore fieldwork carried out by the Leningrad (St. Petersburg) Conservatory between 1968 and 1992. The work sets out to introduce the structural-typological and areal characteristics of previously unknown field materials into scholarly circulation. 13 rhythmic types of wedding songs that are most representative of the Novgorod region are identified and described. The first section of the article presents general Novgorod melodies, whose geographic distribution includes the entire territory of the region and adjacent areas of the Russian NorthWestern Federal District. The melodies of the central, southwestern and eastern areas are described in separate sections. The conclusions obtained as a result of clarifying the distribution of wedding tunes confirm the historical and ethnographic features of the division of Novgorod region previously outlined by researchers. On the basis of connections between the folklore of the southwestern area of the Novgorod region and the traditions of the Smolensk and Pskov regions, this territory may be described as having a “mixed” character, possibly due to its settlement by Ilmen Slav and Krivichi tribes. The wedding songs of the southwest are mainly characterised by caesurised chants having various rhythmic and compositional structures. The most significant characteristics of these melodies are defined by their modal organisation, which is mainly associated with intonations of the vocal-incantatory type. The central and eastern zones, conversely, provide an opportunity to identify the specifically Novgorodian features of wedding folklore, which later developed in the song systems of the Russian North, the Urals, and Siberia. The typological features of the melodies of these territories include their on tonic versification and the lamentable-narrative nature of the intonation. The main development vector of Novgorod wedding traditions turned out to be aimed at strengthening the significance of the initiation line of the ritual, which was reflected in its pre-wedding part. On the basis of the notations and analytical observations presented in the article, the place of Novgorod wedding folklore in the structure of Russian wedding music can be evaluated to provide a basis for further comparative-typological research in the field of ethnomusicology. Keywords: wedding songs, Russian folklore, Novgorod region, melogeography, song type, musical areas, rhythmic type For citation: Korolkova, I. V. (2025). Wedding Songs of the Novgorod Region: To the Issue of the Tunes Territorial Distribution. Contemporary Musicology, 9(2), 214―241. https://doi.org/10.56620/2587-9731-2025-2-214-241